STATE PROPERTY: ANALYSIS, REGULATION, AND DEVELOPMENT PROSPECTS IN UKRAINE, THE EU, AND POST-SOVIET COUNTRIES - Yeleiko, Taras (Socio-economic relations in the digital society, 2024)
The article is dedicated to the analysis of state and municipal property, their structure, and regulation in Ukraine and Central and Eastern European countries. The main objective of the study is to determine the role of state ownership in service provision, control over strategic resources, and support of public welfare, as well as to assess the efficiency of the use and management of state-owned enterprises. The study shows that state ownership plays a key role in sectors such as national security, energy, transportation, education, healthcare, natural resources, and banking. The share of state ownership and its efficiency varies significantly between countries. For instance, in Poland, state-owned enterprises account for about 17% of GDP, while in Romania this figure is only 5-7%. In Ukraine, the share of state-owned enterprises in GDP is approximately 8-10%, with many remaining inefficient. Comparisons with other countries show that the efficiency of state asset management in Ukraine is among the lowest in the region. To improve the efficiency of state ownership in Ukraine, it is necessary to implement better management practices and reduce the share of state property in sectors where the private sector can provide better efficiency. The research results emphasize the importance of reforming state-owned enterprises, particularly through privatization and the implementation of transparent management standards. This will help increase the economic efficiency of state assets, which is critical for ensuring the sustainability of the economy and filling the state budget.